2007
DOI: 10.1021/la7012667
|View full text |Cite
|
Sign up to set email alerts
|

ATR-IR Spectroscopic Study of Antimonate Adsorption to Iron Oxide

Abstract: Antimonate ions adsorb to iron oxides in mining contexts, but the nature of the adsorbed antimonate species has not frequently been investigated. In this study, ATR-IR spectroscopy was used to reveal that the adsorption of Sb(OH)6- ion from aqueous solutions onto an amorphous iron oxide particle film is accompanied by changes in the Sb(OH)6- spectrum and the loss of OH stretching absorptions from iron oxide surface hydroxyl groups. These spectral changes upon adsorption imply an inner-sphere surface interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(48 citation statements)
references
References 29 publications
5
43
0
Order By: Relevance
“…A chemical interaction occurs and forms a new Sb-O-Fe bond, and the preferential adsorption of Sb(V) onto HFO-related hybrids are mainly attributed to the inner-sphere complexation of Sb(V) with HFO. A similar result was obtained by Mccomb et al [87]. FTIR spectra revealed that the shifts in the absorbance of hydroxyl groups in iron oxide were related to the formation of Fe-O-Sb bonds and provided evidence on inner-sphere bond formation [88].…”
Section: Ftir Analysissupporting
confidence: 80%
“…A chemical interaction occurs and forms a new Sb-O-Fe bond, and the preferential adsorption of Sb(V) onto HFO-related hybrids are mainly attributed to the inner-sphere complexation of Sb(V) with HFO. A similar result was obtained by Mccomb et al [87]. FTIR spectra revealed that the shifts in the absorbance of hydroxyl groups in iron oxide were related to the formation of Fe-O-Sb bonds and provided evidence on inner-sphere bond formation [88].…”
Section: Ftir Analysissupporting
confidence: 80%
“…This corroborated the highly nonlinear Sb(V) sorption behavior indicated by low values of the Freundlich N (Table 1). Earlier studies show that Sb(V) released more rapidly at higher pH from iron oxide (McComb et al, 2007) and kaolinite (Xi et al, 2010) as a result of low sorption affinity. But in our reaction, the desorption were performed by successive dilution with same background solution of 0.01 M KClO 4 and the reaction pH gradually approached equilibrium, which explains the relatively stable fraction of desorption with respect to initial solution pH.…”
Section: Kinetic Sorption-desorptionmentioning
confidence: 96%
“…The kinetics of Sb(III) and Sb(V) adsorption on the Al-rich minerals is a relatively slow process extended to 720 h (Ilgen and Trainor, 2012), while kinetic rate of Sb(V) adsorption on bentonite was rapid initially and slowly approaching steady state after roughly 24 h (Xi et al, 2011). Spectroscopic study of Sb(V) adsorption/desorption to amorphous Fe oxide showed more rapid desorption under alkaline conditions (McComb et al, 2007). The kinetic batch experiments conducted by Martinez-Llado et al (2011) have shown Sb(V) sorption on calcareous soils was relatively slow and follows a pseudo-second order rate equation.…”
Section: Introductionmentioning
confidence: 96%
“…Surface complexation modeling conducted for Sb(III) and Sb(V) adsorption on iron rich red earth suggested the formation of bidentate mononuclear and binuclear complexes (Vithanage et al, 2013). Several studies have confirmed the strong influence of pH on Sb(V) sorption on Fe hydroxides with sorption maxima at low pH values and decreases after pH 7 (Tighe et al, 2005;Leuz et al, 2006;McComb et al, 2007). Sorption studies showed that large fractions of Sb sorbed on soils were nonexchangeable by ionic solution, suggesting the low mobility of Sb in soils (Hammel et al, 2000;Ettler et al, 2007).…”
Section: Introductionmentioning
confidence: 96%